2020
DOI: 10.3390/agronomy10040509
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Head Blight, Mycotoxins and Strategies for Their Reduction

Abstract: Mycotoxins are secondary metabolites of microscopic fungi, which commonly contaminate cereal grains. Contamination of small-grain cereals and maize with toxic metabolites of fungi, both pathogenic and saprotrophic, is one of the particularly important problems in global agriculture. Fusarium species are among the dangerous cereal pathogens with a high toxicity potential. Secondary metabolites of these fungi, such as deoxynivalenol, zearalenone and fumonisin B1 are among five most important mycotoxins on a Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 227 publications
(315 reference statements)
2
77
0
1
Order By: Relevance
“…mycelia, which induces their decay and reduces the efficiency of nutrient and water absorption, while FHB is manifested by the bleaching of spikelets (Xu and Nicholson 2009). Some Fusarium species are among the dangerous cereal pathogens with its secondary metabolites such as deoxynivalenol (DON), zearalenone (ZEN), and fumonisin B1, that are among the five most important mycotoxins (Mielniczuk and Skwaryło-Bednarz 2020). Investigations carried out revealed that strains of F. culmorum was the dominant and most aggressive species on wheat seedlings associated with FCR and FHB in Algeria (Abdallah-Nekache et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…mycelia, which induces their decay and reduces the efficiency of nutrient and water absorption, while FHB is manifested by the bleaching of spikelets (Xu and Nicholson 2009). Some Fusarium species are among the dangerous cereal pathogens with its secondary metabolites such as deoxynivalenol (DON), zearalenone (ZEN), and fumonisin B1, that are among the five most important mycotoxins (Mielniczuk and Skwaryło-Bednarz 2020). Investigations carried out revealed that strains of F. culmorum was the dominant and most aggressive species on wheat seedlings associated with FCR and FHB in Algeria (Abdallah-Nekache et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has often been reported that the presence of Fusarium spp. and related mycotoxin production depends, amongst others, on agronomic practices like crop rotation, the soil cultivation, the susceptibility of the cultivar and the use of fungicides against FHB (Beyer et al 2006;Janssen et al 2019;Mielniczuk and Skwaryło-Bednarz 2020;van der Fels-Klerx et al 2010;Zorn et al 2017). Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium spp. infections and DON are frequently seen on wheat when it is cultivated after maize or wheat together with minimum tillage of the soil, leaving organic residues from the previous crop (Birr et al 2019;Mielniczuk and Skwaryło-Bednarz 2020). However, effects of specific agronomic measures might vary between countries.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is most often caused by F. graminearum and F. culmorum and in recent years also by F. poae. The participation of individual species in causing FHB is highly dependent on weather conditions [ 14 , 15 , 16 ]. Aspergillus flavus , as well as Fusarium spp., can contaminate the colonized grains with several classes of mycotoxins, secondary metabolites dangerous to human and animal health, severely affecting yield production and lowering the quality and safety of the final products [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%